Sic transit gloria mundi – crypts of selected southern landscapes of the Southern Wielkopolska - Prałat, Emilian (In the Mirror of Things, 2022)
The aim of the article is to present the history of selected crypts of the gentry families of southern Wielkopolska: Brodnica (belonging to the Koźmian and Chłapowski families); Głuchowo (Żółtowski family); Łęki Wielkie (Kęszycki family). The text takes up the topic of the typology of crypts, their creation and expansion, the variety of forms, decoration of coffins, artistic expression, symbolic and cultural meaning. The specificity of Wielkopolska crypts is associated with a very strong sense of attachment to the family property, therefore establishing ancestral necropolises served to strengthen the emotional ties with the region. In selected cases, the construction of the crypts was of prestigious importance, as in the case of the Koźmianów crypt in Brodnica, which was located near the burial of the creator of the Polish anthem, Józef Wybicki. The crypt, as a special form of a cemetery, has grown into multiple associations that are subject to modification. The contextual background for the analyzes is the tradition of funeral patriotic and anniversary celebrations widespread in Wielkopolska in the 19th and early 20th centuries. The places analyzed in the text belong to families that are unrelated and relatively distant from each other. However, they testify to the existence of a common funeral pattern. The fact that two of the three crypts have been used continuously since the beginning of the 19th century proves the durability of the tradition of this type of burial.